Comparative analysis through propensity score matching in thyroid cancer: unveiling the impact of multiple malignancies - Al-Ibraheem, Akram; Abdlkadir, Ahmed Saad; Al-Adhami, Dhuha Ali; Lopci, Egesta; Al-Omari, Amal; Al-Masri, Mahmoud; Yousef, Yacoub; Al-Hajaj, Nabeela; Mohamad, Issa; Singer, Susanne; Sykiotis, Gerasimos P. (Frontiers in Endocrinology, 2024)
The incidence of thyroid cancer is on the rise worldwide, with childhood exposure to radiation being the sole acknowledged catalyst for its emergence. Nonetheless, numerous other factors that may pose risks are awaiting thorough examination and validation. This retrospective study aims to explore the malignancies linked to thyroid cancer and contrast the survival rates of those afflicted with a solitary tumor versus those with multiple primary neoplasms (MPN).Methods: This retrospective study examined data from King Hussein Cancer Center (KHCC), Jordan. Among 563 patients diagnosed with thyroid cancer, 30 patients had thyroid malignancy as part of MPN. For a 1:3 propensity score-matched analysis, 90 patients with only a primary thyroid malignancy were also enrolled.Results: Hematologic and breast malignancies were among the most frequent observed cancers alongside thyroid neoplasm. Patients who had MPN were diagnosed at older age, had higher body mass index and presented with higher thyroglobulin antibody levels (p < 0.05 for each). Additionally, MPN patient displayed a stronger family history for cancers (p= 0.002). A median follow-up duration of 135 months unveiled that MPN patients faced a worse 5-year survival compared to their counterparts with a singular neoplasm (87% vs 100% respectively; p < 0.01). However, no distinction emerged in the 5-year event-free survival between these two groups.MPN correlates with a significantly altered survival outcome of thyroid cancer patients. The diagnosis of thyroid carcinoma at an older age, accompanied by elevated initial thyroglobulin antibody levels and a notable familial predisposition, may raise concerns about the potential occurrence of synchronous or metachronous tumors.